Determination of Shear Bond Strength of Nanocomposite to Porcelain and Metal Alloy - Zenab Sarfraz; Zartashia Arooj; Ayesha Fahim; Sadia Manzoor; Mariyah Javed; Asfia Saeed; Abdul Samad Khan; Sohail Abbas Khan; Mohammad Khursheed Alam (Association of Support to Oral Health Research (APESB), 2022)
Objective: To compare porcelain and metal repair done with both nanocomposite and conventional composite. Material and Methods: A total of 30 cylinders were fabricated from Porcelain (I), Porcelain fused to metal (II), and metal (III) substrate each. Control group (A) was bonded with conventional micro-hybrid composite and experimental group (B) was bonded with nanocomposite in a 2 mm thickness. All specimens were thermocycled and stored in distilled water at 37 °C for 7 days. A universal testing machine was used to measure the Shear bond strength (SBS). The difference between bond strengths of the groups was compared using an independent t-test. Results: In all three groups, the SBS was higher in the experimental group as compared to the control group. The use of nanocomposite of metal alloy presented maximum shear bond strength, followed by samples of porcelain fused to metal and finally porcelain, showing the lowest values of SBS. Conclusion: Porcelain and alloys bonded with nanocomposite exhibit enhanced adhesiveness as well as aesthetic and mechanical properties. This subsequently would translate into providing higher clinical serviceability and durability and hence a cost-effective and accessible repair option for human welfare.